Nanoparticle protein corona and its role in disease diagnostic - Fitya Syarifa Mozar (Journal of Applied Pharmaceutical Science, 2022)
In the past decades, nanoparticles (NP) have shown tremendous potential for biomedical applications, such as targeted therapeutics, medical imaging, and biosensors. After administration, NP will directly interact with various biological components in the body, forming a protein corona (PC) on their surface. The PC composition affects the NP identity and behavior, including its stability, targeting ability, cellular uptake, toxicity, biodistribution, and elimination. Thus, a more profound understanding of the nano-bio-interface is crucial to improving the NP design for theranostic applications. The personalized PC (PPC) concept allows specific PC characteristics identification for early disease diagnosis and personalized therapeutics. However, accurate PC characterization is challenging due to its dynamic and complex nature. Until now, most studies have been focused on the NP PC characterization in vitro yet put less emphasis on its translational aspects. In this mini-review, the author will discuss various challenges surrounding PPC research, strategies to bridge that gap, clinical relevance, and future outlook. PPC’s application for biomarker discoveries and recent advances in PPC analysis methodologies such as multiomics approach, Proteograph workflow, and machine learning algorithm will also be explored. Overall, PPC technology keeps evolving, and it holds a promising future in the personalized medicine era.
Keywords: Nanoparticles (NP), protein corona (PC), personalized protein corona (PPC), nano-bio-interface, Proteograph